Reflections on agricultural landscape revegetation in south‐eastern Australia: Interview with Martin Driver. (15th September 2015) - Driver, Martin; McDonald, Tein
Abstract : One of Australia's leading on‐ground extension officers describes the successes and lessons learned in The Riverina's native revegetation movement over the 20–25 years – but warns of potential failure of current and future Australian revegetation programs if greater funding security is not delivered.